The benefit of pulmonary rehabilitation against quality of life alteration and functional capacity of chronic obstructive pulmonary disease patient assessed using St Georgeâs respiratory questionnaire and 6 minutes walking distance test (Medical Journal of Indonesia, 2006)
Patients with chronic obstructive pulmonary disease (COPD) have been shown to be benefit from pulmonary rehabilitation programs. We assessed an entirely outpatient-based program of pulmonary rehabilitation in patients with COPD, using the St Georgeâs Respiratory Questionnaire (SGRQ) and six minutes walking distance test (6MWD) (which measures health-related quality of life and functional exercise tolerance) as the primary outcome measure. We undertook a randomized, opened, prospective, parallel-group controlled study of outpatient rehabilitation program in 56 patients with COPD (52 men and 4 women). The active group (n=27) took part in a 6-weeks program of education and exercise. The control group (n=29) were reviewed routinely as medical outpatients. The SGRQ and 6MWD were administered at study entry and after 6 weeks. Outcome with SGRQ and 6MWD before and after therapy was performed. Decrease score SGRQ and increase 6MWD in both groups of study, it was analyzed by statistic study and in active group the decrease of SGRQ and the increase of 6MWD was statistically significant. In conclusion 6-weeks outpatient-based program significantly improved quality of life and functional capacity in mild-to-moderate COPD patient. (Med J Indones 2006; 15:165-72) Keywords: COPD, pulmonary rehabilitation, SGRQ, 6MWD